Co-production of Hydrogen and Methane From the Organic Fraction of Municipal Solid Waste in a Pilot Scale Dark Fermenter and Methanogenic Biofilm Reactor - Yeshanew, Martha M.; Paillet, Florian; Barrau, Carole; Frunzo, Luigi; Lens, Piet N. L.; Esposito, Giovanni; Escudie, Renaud; Trably, Eric (Frontiers in Environmental Science, 2018)
The co-production of biohydrogen and methane from the organic fraction of municipal solid waste was investigated using a two-stage AD system, composed of a pilot scale dark fermenter (DF) and a continuous methanogenic biofilm reactor. From the DF process, a biohydrogen yield of 41.7 (± 2.3) ml H₂/gVSadded was achieved. The liquid DF effluent (DFE) was rich in short chain volatile fatty acids, i.e. mainly acetic and butyric acid. The DFE was valorized by producing methane in the methanogenic biofilm reactor. Two methanogenic biofilm reactors were used to assess the biotic and abiotic role of the DFE on the performance of the reactors. Regardless of the different DFE feeding (i.e. biotic and abiotic), similar and stable operational performance of the two methanogenic biofilm reactors were observed with a respective methane yield and COD removal efficiency of 280-300 ml CH₄/gCODremoved and 80-90 %. Both methanogenic biofilm reactors showed significant resistance towards organic shock loads and recovered faster after reactor disturbance. The total estimated energy recovered in the form of hydrogen and methane gas was, respectively, 28 % and 72 %, of the initial COD.